Vaccinating pregnant women against influenza needs to be a priority for all countries: An expert commentary. (March 2020) - Buchy, Philippe; Badur, Selim; Kassianos, George; Preiss, Scott; Tam, John S.
Graphical abstract: Highlights: Vaccination reduces hospitalisation and death due to influenza in pregnant women. Antenatal influenza vaccination reduces the risk of foetal death and preterm birth. Antenatal influenza vaccination protects newborns for the first months of life. Education of care givers and pregnant women increases influenza vaccination uptake. Abstract: Background: In 2012, the World Health Organization recommended influenza vaccination for all pregnant women worldwide and the prioritisation of pregnant women in national influenza vaccination programmes. Nevertheless, vaccination rates in pregnant women often remain much lower than national targets. Objectives: To assess the benefits and risks associated with influenza infection and vaccination during pregnancy, and to consider obstacles that work against influenza vaccine uptake during pregnancy. Results: There is strong evidence that maternal and foetal outcomes can be compromised if women develop influenza infections during pregnancy. Influenza vaccines have been administered to millions of pregnant women and have demonstrated benefits in terms of disease prevention in mothers and their infants. There is a consensus amongst several recommending authorities that influenza vaccines may be safely administered during all stages of pregnancy. Healthcare professionals are recognised as the most important influencers of vaccine uptake, being well placed to recommend vaccination and directly address safety concerns. Conclusions: Despite data supporting the value of influenza vaccination during pregnancy, vaccine uptake remains low globally. Low uptake appears to be largely due to ineffective communication with pregnant women about the risks and benefits of influenza vaccination. A graphical abstract is available online.